European territorial cooperation towards territorial cohesion? - Medeiros, E.; Scott, J.; Ferreira, R.; Boijmans, P.; Verschelde, N.; Guillermo-Ramírez, M.; Gyula, O.; Peyrony, J.; Soares, A. (Regional Studies, 2024)
Understood in some conceptual analysis as a pillar of territorial cohesion and due to its critical role in promoting territorial integration, territorial cooperation is often presented as one of the major positive achievements of European Union (EU) Cohesion Policy. In this context, this article proposes a conceptual framework to assess the contribution of the European Territorial Cooperation process, including the beyond-funding support from the Border Focal Point, to the ultimate goal of EU Cohesion Policy: territorial cohesion. For that, expertise from the leaders of European cross-border associations is used, as well as European Commission officials.